(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2012)
Taking cue from the epistolary exchange between Gottfried Boehm and Tom Mitchell, the article explores the relationship between the so-called Bildkritik and the visual semiotics. Rather than focusing on the explicit quotation of semiotic concepts or authors, the paper proposes to examine the heuristic approach to the image that characterizes both the analytical dimension of the Bildkritik and the semiotics of the image developed by the French generative semiotics. Taking into account the immanent approach of both traditions and some key-operators (such as ‘iconic difference’ and ‘sémiotique plastique’), the acknowledgement of an active sense-generating capability of the ‘visual’ will emerge as a common feature.